The EU-China bilateral investment agreement in negotiation: Motivation, conflicts and perspectives - Frank Bickenbach; Wan-Hsin Liu; Guoxue Li (Kiel Institute for the World Economy (IfW), 2015)
Since January 2014 China and the European Union (EU) have been negotiating a comprehensive bilateral investment agreement. In contrast to the EU-US negotiations on a Transatlantic Trade and Investment Partnership (TTIP), the ongoing negotiations between China and the EU have received little public attention so far. Still, a successful conclusion of these negotiations may be of great importance even beyond the EU-China investment relations. This holds in at least two respects. Firstly, a successfully concluded bilateral investment agreement may pave the way for a future EU-China free trade agreement. And secondly, looking beyond the bilateral relationship, the negotiations between the EU and China may make an important contribution to the establishment of a more liberal global investment framework. Currently, China is also negotiating an investment agreement with the US which is likely to take a similar form as that between China and the EU. In addition, provisions for the future liberalisation of bilateral investment flows are also an important part of the TTIP negotiations between the US and Europe. Rules and provisions, e.g., regarding market access, the prohibition of performance requirements or the transparency with respect to state-owned enterprises, that are part of all three agreements will "be elevated to a de facto global standard" (Berger 2014). Against this background, the present Kiel Policy Brief analyses the key barriers investors from China and the EU currently face in the EU and China, respectively and provides a brief assessment of whether and how these key barriers can be dealt with in the comprehensive EU-China investment agreement currently negotiated.
Keywords: 330